2006
DOI: 10.1002/jbm.b.30531
|View full text |Cite
|
Sign up to set email alerts
|

Octacalcium phosphate combined with collagen orthotopically enhances bone regeneration

Abstract: Octacalcium phosphate (OCP) is resorbable bone regenerative material, but its brittleness makes it difficult to maintain its shape without restraint. We have engineered a scaffold constructed of synthetic OCP and porcine collagen sponge (OCP/Collagen) and investigated whether OCP/Collagen composite could improve bone regeneration. To examine this hypothesis, bone regeneration by the implantation of OCP/Collagen was compared with those by OCP and collagen. Radiographic and histological examination was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 49 publications
6
131
2
Order By: Relevance
“…We previously showed that OCP/Col disks induce bone regeneration better than collagen disks (Kamakura et al, 2006;Kawai et al, 2009). Interestingly, in the present study we found that OCP/Col disks implanted without MSCs into bone defects enhanced bone regeneration better than collagen disks with MSCs (Figs.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We previously showed that OCP/Col disks induce bone regeneration better than collagen disks (Kamakura et al, 2006;Kawai et al, 2009). Interestingly, in the present study we found that OCP/Col disks implanted without MSCs into bone defects enhanced bone regeneration better than collagen disks with MSCs (Figs.…”
Section: Discussionsupporting
confidence: 57%
“…3. It has been previously shown that soft x-ray conditions used for measurement do not exhibit any radiopacity in OCP/ Col disks before implantation (Kamakura et al, 2006). OCP/Col·MSCs and OCP/Col disks implanted in a rat calvaria defect showed radiopacity at 4 and 8 weeks postimplantation.…”
Section: Bone Regeneration By the Ocp/col Scaffold Se Eded With Osteomentioning
confidence: 95%
See 2 more Smart Citations
“…[742][743][744]783,[785][786][787][788] These biomaterials mimic natural bones to some extent, while their subsequent biological evaluation suggests that they are readily incorporated into the bone metabolism in a way similar to bone remodeling instead of acting as permanent implant. 609,731 However, the performance of these biocomposites depends on the source of the collagen from which it was processed.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%